Quantification of peptides from immunoglobulin constant and variable regions by LC‐MRM MS for assessment of multiple myeloma patients. Issue 10 (15th September 2014) - Remily‐Wood, Elizabeth R.; Benson, Kaaron; Baz, Rachid C.; Chen, Y. Ann; Hussein, Mohamad; Hartley‐Brown, Monique A.; Sprung, Robert W.; Perez, Brianna; Liu, Richard Z.; Yoder, Sean J.; Teer, Jamie K.; Eschrich, Steven A.; et al.
Abstract : Purpose: Quantitative MS assays for Igs are compared with existing clinical methods in samples from patients with plasma cell dyscrasias, for example, multiple myeloma (MM). Experimental design: Using LC‐MS/MS data, Ig constant region peptides, and transitions were selected for LC‐MRM MS. Quantitative assays were used to assess Igs in serum from 83 patients. RNA sequencing and peptide‐based LC‐MRM are used to define peptides for quantification of the disease‐specific Ig. Results: LC‐MRM assays quantify serum levels of Igs and their isoforms (IgG1–4, IgA1–2, IgM, IgD, and IgE, as well as kappa (κ) and lambda (λ) light chains). LC‐MRM quantification has been applied to single samples from a patient cohort and a longitudinal study of an IgE patient undergoing treatment, to enable comparison with existing clinical methods. Proof‐of‐concept data for defining and monitoring variable region peptides are provided using the H929 MM cell line and two MM patients. Conclusions and clinical relevance: LC‐MRM assays targeting constant region peptides determine the type and isoform of the involved Ig and quantify its expression; the LC‐MRM approach has improved sensitivity compared with the current clinical method, but slightly higher inter‐assay variability. Detection of variable region peptides is a promising way to improve Ig quantification, which could produce a dramatic increase in sensitivity over existing methods, and could further complement current clinical techniques.